Reviewer in management advisory services - Agamata, Franklin T. (Recto, Manila : GIC Enterprises & Co. Inc., 2012)
Summary: This reviewer aims to help examinees in their successful preparation for the RP CPA Board Examinations, specifically in the field of management advisory services.
1. MAS environment and practice standards -- 2. Management accounting and its environment -- 3. Cost concepts, classification and segregation -- 4. Variable costing -- 5. Profit planning and cost volume profit analysis -- 6. Short-term budgeting -- 7. Standard costing and variance analysis -- 8. Responsibility accounting, segment reporting and transfer pricing -- 9. Short term non routine decisions -- 10. Quality environment and strategic management -- 11. Strategic management accounting -- 12. Profit and market variance analysis -- 13. Financial statement analysis -- 14. Cost of capital -- 15. Capital budgeting -- 16. General working capital management -- 17. Cash and marketable securities management.
Keywords: MANAGEMENT -- STANDARDS